PERANCANGAN E - JURNAL KELAS MA NU ISLAMIYAH BERBASIS WEBSITE - Arika Zehrotul Fitriyah; Moh. Raihan Mostofa; Nor Dina Kamilia; Wulidatul Nursa'bani; Abd. Samad (Jurnal Riset Teknik Komputer, 2026)
Advancements in information technology are driving educational institutions to digitize academic administration to enhance the effectiveness and efficiency of data management. At MA NU Islamiyah Asembagus, the class journal remains an aspect of academic administration handled manually. Recording entries in a physical journal book complicates data retrieval and report compilation, while also posing risks of document loss or damage. This study aims to design a web-based Class E-Journal system prototype capable of supporting more effective and integrated instructional administration management. The research methodology employed includes observation, interviews, documentation review, and a literature study. System development utilized the prototyping method, comprising stages for requirements analysis, system design, prototype creation, prototype evaluation, implementation, and system testing. The system design incorporates Context Diagrams, Data Flow Diagrams (DFD), and Entity-Relationship Diagrams (ERD). Research results indicate that the Class E-Journal system prototype facilitates the integrated management of class schedules, teaching journal entries, and report compilation. User evaluations confirm that the system design aligns with the school's instructional administration needs. The system is expected to support digital transformation and improve the effectiveness of academic administration management at MA NU Islamiyah Asembagus.